A educação jesuítica no Brasil e a formação religiosa e pastoral durante a pandemia: a experiência do Colégio Antônio Vieira - Justa, José William Tavares (Universidade do Vale do Rio dos Sinos, 2021)
This study aims to discuss how the “projeto de Serviço de Orientação Religiosa e Pastoral – SORPA” in Colégio Antonio Vieira, in Salvador, has promoted, during the pandemic, the humanistic and transforming service contained in the proposal for social justice defended by the Jesuits over the centuries, and walking in the realization of the postulates that such documents propose. For this, it was necessary to conduct a bibliographical research, based on the Service Project, its reports and other documents. To support this discussion, studies that deal with Jesuit education in Brazil and in Bahia were used, as well as the formal education provided by the Catholic religious schools maintained by this group, in particular, Colégio Antonio Vieira – CAV.
Keywords: Educação religiosa; Jesuítas; Formação cidadã; Religious education; Jesuits; Citizen formation